A dinosaur ate my homework - Nelson, Ray, 1965-; Kelly, Douglas, 1955-; Adams, Ben (Children's story writer) (New York : Scholastic Inc., 1997)
Facts about different kinds of dinosaurs accompany a story about a boy who brings various prehistoric animals to school for show-and-tell.
"With the cooperation of Raymond T. Rye, National Museum of Natural History, Smithsonian Insitution."
Logo on t.p.: Dinosaurs, Flying Rhinosaurus.
Reprint of the 1996 Flying Rhino ed.
Keywords: Dinosaurs -- Juvenile fiction; Schools -- Juvenile fiction; Dinosaurs -- Fiction; Schools -- Fiction; Stories in rhyme